The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.24843/jaa.2017.v06.i03.p09
|View full text |Cite
|
Sign up to set email alerts
|

Analisis Risiko Usahatani Salak Organik di Desa Sibetan Kecamatan Bebandem Kabupaten Karangasem

Abstract: The Risk Analysis of Zallaca Organic Farming in Sibetan Village Subdistrict Bebandem Karangasem Regency Sibetan village is a development center of zallaca organic farming in subdistrict Bebandem, Karangasem regency. The problems that have been faced by zallaca organic farming like a fluctuation of production and commodity prices, thus indicating the risk that must be faced by the farmers related to production and the selling price of the commodity in the market. If production and price has a risk, it wil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…This value indicates a very low parameter because the CV value is 0.5. This is in accordance with (Mahayani et al, 2017) research which states that the coefficient of variation in salak production is 0.5, which means that every 100 harvests, there is a chance that the harvest will fail 50 times from the expected production. Another study from (Pratiwi et al, 2019) stated that the risk of salak pondoh production was 0.04.…”
Section: Coefficient Of Variation (Cv) and Lower Limit Value (L)supporting
confidence: 90%
See 1 more Smart Citation
“…This value indicates a very low parameter because the CV value is 0.5. This is in accordance with (Mahayani et al, 2017) research which states that the coefficient of variation in salak production is 0.5, which means that every 100 harvests, there is a chance that the harvest will fail 50 times from the expected production. Another study from (Pratiwi et al, 2019) stated that the risk of salak pondoh production was 0.04.…”
Section: Coefficient Of Variation (Cv) and Lower Limit Value (L)supporting
confidence: 90%
“…Although the labor variable does not have a significant effect on reducing risk because in the cultivation of salak pondoh does not require intensive care. In salak pondoh farming the most needed labor is for pollination pruning and fruit thinning (Mahayani et al, 2017). If more intensive care of salak pondoh especially for pruning, pollination, and thinning, the risk of production can be reduced.…”
Section: Causes Of Reduced Riskmentioning
confidence: 99%
“…Tinjauan Pustaka 1. Konsepsi Agrowisata Agrowisata sebagai salah satu alternatif pariwisata berkelanjutan merupakan bagian dari objek wisata yang memanfaatkan usaha pertanian (agro) sebagai wisata yang bertujuan untuk memperluas pengetahuan, pengalaman, rekreasi dan usaha di bidang pertanian pengembangan yang memanfaatkan lahan berdasarkan budaya lokal ini diharapkan dapat meningkatkan pendapatan petani serta untuk cadangan sumberdaya tanah, serta memelihara budaya lokal serta teknologi lokal (pengetahuan masyarakat adat) yang pada umumnya sesuai dengan kondisi alam lingkungan (Adnyani, dkk, 2015).…”
Section: Kerangka Teoritisunclassified
“…The higher the confidence in the skills and knowledge possessed, the greater the individual's desire to obtain a high and unlimited income. In some cases, it is found that high income expectations will cause self-confidence to decrease because individuals realize that the skills and knowledge they have cannot realize their expectations of the desired income (Mahayani et al, 2017;Sintya, 2019).…”
Section: The Impact Of Income Expectations On Self-efficacymentioning
confidence: 99%
“…The income (income) of each type of work must vary, this difference is due to how many production factors the individual sells to the company and how much risk it will experience (Sintya, 2019). The greater the risk of a job usually offers a high salary as well as high risk high return, choosing a career as an entrepreneur must have great risks but offers a high income (Mahayani et al, 2017). Individuals who have attended Entrepreneurship Education and Training (EET) will have high income wishful thinking, and have skills that can be applied to their business so that they can achieve the income they want (Chereau & Meschi, 2021).…”
Section: The Impact Of Income Expectations On Entrepreneurial Interes...mentioning
confidence: 99%